Involvement of the secreted protein Metrnl in human diseases - Miao Zhu-wei; Hu Wen-jun; Li Zhi-yong; Miao Chao-yu (Acta Pharmacologica Sinica, 2020)
Metrnl, a secreted protein expressed in white adipose tissue, has been identified as a novel adipokine. It is also highly expressed in barrier tissues, including the skin, intestinal and respiratory tract epithelium in both mice and humans. Research shows that its expression is upregulated by inflammation, chronic high-fat diets, exercise, cold exposure, etc., and it plays important roles in promoting neurite extension, enhancing white fat browning, improving insulin sensitivity, modulating lipid metabolism and regulating inflammatory response, the latter implying Metrnl is a new cytokine. These studies suggest that Metrnl could be a promising biomarker and a potential therapeutic target for the related diseases. For proving this, clinical studies need to be performed to bridge the gap between bench and bedside. In this paper, we summarize the progress in recent clinical research on Metrnl. Most of these clinical studies are designed to confirm the relationship between circulating Metrnl and metabolic or cardiovascular disease (type 2 diabetes and coronary heart disease), or immune inflammation-related diseases, such as colitis, psoriasis and arthritis. Although blood Metrnl seems to fluctuate and are affected by many factors, such as drugs, physical exercise, and cold exposure, these clinical studies provide reliable clues that Metrnl is associated with coronary heart disease, inflammation- related diseases, etc. Nevertheless, the roles of Metrnl in some diseases such as nervous system diseases remain unclear, and its putative involvement should be further clarified. These studies could promote the application of Metrnl in clinic as a new therapeutic target.